Core–shell droplets and microcapsules formed through liquid–liquid phase separation of a colloid–polymer mixture. Issue 36 (31st August 2021) - Dang, Steven; Brady, John; Rel, Ryle; Surineni, Sreenidhi; O'Shaughnessy, Conor; McGorty, Ryan
Abstract : A temperature-responsive colloid–polymer system undergoes liquid–liquid phase separation and forms all-aqueous core–shell droplets and microcapsules. Abstract : Microcapsules allow for the controlled containment, transport, and release of cargoes ranging from pharmaceuticals to fragrances. Given the interest from a variety of industries in microcapsules and other core–shell structures, a multitude of fabrication strategies exist. Here, we report on a method relying on a mixture of temperature-responsive microgel particles, poly( N -isopropylacrylamide) (pNIPAM), and a polymer which undergo fluid–fluid phase separation. At room temperature this mixture separates into colloid-rich (liquid) and colloid-poor (gas) fluids. By heating the sample above a critical temperature where the microgel particles shrink dramatically and develop a more deeply attractive interparticle potential, the droplets of the colloid-rich phase become gel-like. As the temperature is lowered back to room temperature, these droplets of gelled colloidal particles reliquefy and phase separation within the droplet occurs. This phase separation leads to colloid-poor droplets within the colloid-rich droplets surrounded by a continuous colloid-poor phase. The gas/liquid/gas all-aqueous double emulsion lasts only a few minutes before a majority of the inner droplets escape. However, the colloid-rich shell of the core–shell droplets can solidify with the addition of salt. That this method creates core–shell structures with a shell composed of stimuli-sensitive microgel colloidal particles using only aqueous components makes it attractive for encapsulating biological materials and making capsules that respond to changes in, for example, temperature, salt concentration, or pH.